Neuropsychological and electrophysiological long-term follow-up in the adult form of Niemann-Pick disease type C. Issue 1 (January 2019) - Tozza, S.; Dubbioso, R.; Iodice, R.; Topa, A.; Esposito, M.; Ruggiero, L.; Spina, E.; Iovino, A.; Santoro, L.; Manganelli, F.
Abstract : Niemann-Pick disease type C (NPC) is a recessive lysosomal lipid storage disorder characterized by central nervous system involvement. Miglustat treatment might improve or stabilize neurological manifestations but there is still limited data on the long-term efficacy. The aim of our study was to report a four-year clinical, neuropsychological and electrophysiological follow-up of two sisters under treatment with miglustat. We report data at basal (T0) and after 4 years (T4) of treatment with miglustat from two sisters (P1 and P2) affected by NPC disease. During the follow-up period, P1 was not adherent to treatment. Both patients underwent neurological evaluation, neuropsychological assessment, nerve conduction study and motor (MEP), visual (VEP), somatosensory and brainstem auditory evoked potentials. In the patient P2, neurological and electrophysiological evaluations at T4 were stable. Instead, the patient P1, with poor adherence to therapy, developed spasticity, psychiatric disturbances and alterations of MEP and VEP. Neuropsychological examination showed in both patients a worsening of cognitive impairment. Our findings suggest that long-term therapy with miglustat does not arrest cognitive decline, otherwise it stabilizes other neurological manifestations.